1851. Recurrence of Streptococcus agalactiae Bacteremia - Risk Factors and Complications. (15th December 2022) - Wang, Taylor B; Zimilover, Adam; Garellek, Jonathan; Mahvish, Gull; Parvez, Hina; Given, Hafsa No Name; Singh, Damanbir; Patel, Pranavkumar; Patel, Pranavkumar; Gorlin, Margaret; Kim, Angela; Flannery, Sarah; et al.
Abstract: Background: The primary objective was to identify the frequency of recurrent Streptococcus agalactiae (GBS) bacteremia and associated risk factors for recurrence. The secondary objective was to determine the source of the initial GBS bacteremia and complications. Methods: This was a retrospective observational study evaluating patients who were admitted to any of the 12 hospitals within the Northwell Health System from 1/1/2016 to 1/1/2020. Non-pregnant patients ≥ 18 years of age with GBS bacteremia were included. Recurrence was defined as admission due to GBS bacteremia within 1 year after a positive blood culture. Statistical methods performed include t-test or Wilcoxon Rank Sum test, Chi-square, Fisher exact tests, and both univariable and multivariable logistic regressions. Results: 390 patients met inclusion criteria with a median age of 63 years old. Majority were white (61.5%) and male (54.1%). Recurrence was found in 18 of 390 patients (4.62%). There was a significant increase in recurrence for patients allergic to penicillin or cephalosporins (p< 0.03), patients with implantable cardiac devices (ICDs) (p< 0.03) and patients who did not receive β-lactams and/or vancomycin as initial treatment (p< 0.05). 6 of the 18 patients were allergic to penicillin or cephalosporins. The estimated odds of recurrence in patients with ICDs were ∼5.4 times the odds of those without ICDs controlling for allergies (p< 0.04, 95% CI 1.7 – 20.0) or controlling for initial antimicrobial treatment (p< 0.04, 95% CI 1.5 – 18.7). The most common sources of GBS bacteremia were skin and soft tissue (35.1%), unknown (27.9%), and urinary tract (6.41%). Endocarditis was diagnosed in 8 patients (2.05%) via transesophageal echocardiogram. Other complications of GBS bacteremia included vertebral osteomyelitis (3.08%), epidural abscess (0.77%), and septic arthritis (0.77%). Median treatment duration was 15 days, with no significant difference in recurrence (p=0.75). Conclusion: GBS bacteremia recurred in 4.62% of patients. Recurrence was significantly associated with ICDs, penicillin or cephalosporin allergies, and not receiving β-lactam and/or vancomycin-based regimens as initial therapy. The substantial rate of recurrent GBS bacteremia has important clinical implications. Disclosures: All Authors : No reported disclosures.